Implementasi Kurikulum Merdeka di SMA Gloria Jaya Jambi - Rahmadea Novriana; Dion Ginanto (UIN Sulthan Thaha Saifuddin Jambi, 2024)
The Merdeka Curriculum is part of an effort to align Indonesia’s education system with the needs and developments of the times. One of the implementations of the Merdeka Curriculum is carried out in schools, including in the Islamic Religious Education (PAI) subject. As we know, PAI plays a crucial role in shaping the moral and spiritual character of students. This research aims to analyze the implementation of the Merdeka Curriculum in PAI at senior high schools. The primary focus of this research is to see how far these changes can improve teaching quality, support diverse approaches, and address educational challenges faced by both teachers and students who are the subjects of this study. The method used in this research is a qualitative approach with interview and observation techniques conducted on teachers and students. The research findings indicate significant changes. These include providing teachers with the flexibility to design and plan the learning process and methods, incorporating diverse and creative approaches tailored to students’ needs. The Merdeka Curriculum also provides more space for students to excel not only in academics but also in other areas. Differentiated learning allows students to gain learning experiences that are not solely focused on competencies, as well as addressing challenges that often arise and become concerns in implementing this curriculum.